Compliance of Indian dentists with oral radiology safety measures - Swarna Yerebairapura Math; Devarasa Giriyapura Murugeshappa; Rajeshwari Annigeri; Dheeraj Kalra (Wolters Kluwer Medknow Publications, 2013)
Objectives: The aim of this study was to determine the dentist's knowledge and practice about dose reduction techniques, radiographic equipment and quality of dental radiographic service among private dental practitioners in Davangere City, India. Materials and Methods: The survey was performed on 80 dental practitioners from Davangere City, India. Information on the demographic characteristics of the dentists, radiographic equipment, techniques and processing they used and radiation protection was obtained with a 40 point questionnaire. Results: The study yielded a response rate of 90%. The respondents' knowledge concerning the technical details of their equipment was limited, with 27.7% not knowing kVp settings of their equipment. Only 11% and 5% respondents reported having long and rectangular collimators respectively. Regarding the film speed 16.6% dental practitioners were unaware about it. The most preferred technique (81%) for periapical radiography was the bisecting angle technique. Lead aprons were worn more often by female dentists. None of the dental practitioners had thyroid collars. The distance of the dentist to the radiation tube during exposure was on average 2.2 m, although 13% of the dentists assisted in holding the image receptor inside the patient's mouth. Only 4% of the dental practitioners reported that they used automatic processor. About 40% of the dental practitioners used film badges. Conclusions: In the present study, the results indicate that for minimizing any unnecessary radiation, attempts should be made to improve dentists' knowledge about radiation dose reduction techniques. Some dose-reducing strategies are commonly used in Davangere Dental clinics, whereas others have not gained wide acceptance.